Gynecological cancer inpatients need more supportive nursing care than outpatients: a comparative study - Tina Mawardika; Yati Afiyanti; Hayuni Rahmah (BMC, 2019)
Abstract Background Gynecological cancer inpatients and outpatients may have distinct supportive nursing care needs. This study aimed to compare the supportive care needs between these two patient cohorts. Methods This cross-sectional comparison analytic study aimed to identify the differences between the supportive nursing care needs of the gynecological cancer inpatients and outpatients. Data were collected from 200 participants who were recruited through consecutive sampling method. Results The results showed that gynecological cancer inpatients needed more supportive nursing care than the outpatients. The most reported supportive nursing care needs of the inpatients were in the domains of physical (80%) and the psychological (84%). Whilst, the outpatients needed more health information support (78%). There was a significant difference between the supportive nursing care needs of gynecological cancer inpatients and outpatients (p value = 0.001). Supportive nursing care needs of the inpatients were 44 times higher compared to those of the outpatients. Conclusions The gynecological cancer inpatients and outpatients need supportive nursing care differently. Therefore, nurses should assess supportive care needs of their patients early during the care in each setting so that the intervention could be tailored to the patient's individual needs. Our study findings can help nurses navigate the supportive care needs for gynecological cancer patients receiving inpatient and outpatient care.